SARS-CoV-2 infection among healthcare workers whom already received booster vaccination during epidemic outbreak of omicron variant in Taiwan - Wang-Huei Sheng; Hao-Chun Chang; Sui-Yuan Chang; Ming-Ju Hsieh; Yu-Cheng Chen; Yu-Yun Wu; Sung-Ching Pan; Jann-Tay Wang; Yee-Chun Chen (Journal of the Formosan Medical Association, 2023)
Background/Purpose: Healthcare workers (HCWs) are at risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection due to occupational exposure. We aim to investigate the prevalence and risk factors of SARS-CoV-2 infection among HCWs during epidemic outbreak of omicron variant in Taiwan. Methods: Sequential reserved serum samples collected from our previous study during December 2021 and July 2022 were tested for antibodies against SARS-CoV-2 nucleocapsid protein (NP). Diagnosis of SARS-CoV-2 infection was defined as positive either of anti-SARS-CoV-2 nucleoprotein, rapid antigen test or polymerase chain reaction. Retrospective chart review and a questionnaire were used to access the symptoms and risk factors for SARS-CoV-2 infection. Results: Totally 300 participants (69.3% female) with a median age of 37.9 years were enrolled. A significant increase incidence of SARS-CoV-2 infection was found before and during community outbreak (11.91 versus 230.93 per 100,000 person-days, P < 0.001), which was a trend paralleling that observed in the general population. For 61 SARS-CoV-2 infected participants, nine (14.8%) were asymptomatic. Multivariate analysis revealed recent contact with a SARS-CoV-2 infected household (odds ratio [OR], 7.01; 95% confidence interval [95% CI], 3.70–13.30; P < 0.001) and co-existed underlying autoimmune diseases (OR, 4.46; 95% CI, 1.28–15.51; P = 0.019) were significant risk factors associated with acquisition of SARS-CoV-2 infection among HCWs. Conclusion: Community factors, such as closely contact with SARS-CoV-2 infected individuals and underlying immune suppression status, were significant factors for acquisition of SARS-CoV-2 infection among HCWs. We suggest the application of appropriate infection control measures for HCWs should be maintained to reduce risk of SARS-CoV-2 infection.